1994
DOI: 10.1111/j.1398-9995.1994.tb00768.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of loratadine on pruritus in patients with atopic dermatitis

Abstract: The aim of the study was to assess the therapeutic efficacy of loratadine on pruritus in patients with atopic dermatitis, considering the patients' sensation of itch. Sixteen patients, mean age 24.8 years, with moderate or severe atopic dermatitis were included in a double-blind and placebo-controlled study with a six-period, multi-crossover design. The patients were given 10 mg loratadine or placebo every day, alternating between loratadine and placebo every 2 weeks. The degree of pruritus during the day and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 13 publications
0
31
0
3
Order By: Relevance
“…No significant difference between fexofenadine and placebo in the incidence of adverse events was identified. 47 Loratadine, another potent nonsedative H 1 antihistamine, showed a reduction of pruritus and inflammation in two studies 48,49 of patients with AD, while another study 50 did not substantiate loratadine's antipruritic effects. Langeland et al 48 found a significant effect with loratadine in patients with moderate and severe AD compared with placebo on pruritus during the day, pruritus during the night, and severity of the rash.…”
Section: Second-generation Antihistaminesmentioning
confidence: 99%
“…No significant difference between fexofenadine and placebo in the incidence of adverse events was identified. 47 Loratadine, another potent nonsedative H 1 antihistamine, showed a reduction of pruritus and inflammation in two studies 48,49 of patients with AD, while another study 50 did not substantiate loratadine's antipruritic effects. Langeland et al 48 found a significant effect with loratadine in patients with moderate and severe AD compared with placebo on pruritus during the day, pruritus during the night, and severity of the rash.…”
Section: Second-generation Antihistaminesmentioning
confidence: 99%
“…Reported improvements in disease severity and quality of life may be due primarily to promotion of restful sleep rather than a reduction in symptoms. [104][105][106][107][108][109][110][111] In an evidence-based review of the literature from 1966 to 1999, Klein and Clark 104 remarked on the paucity of proper clinical trials and concluded that there is no evidence to support the efficacy of non-sedating antihistamines in AD. Antihistamines are safe and not associated with significant adverse effects, even in very young patients.…”
Section: Discussionmentioning
confidence: 99%
“…Antihistamines are safe and not associated with significant adverse effects, even in very young patients. [106][107][108][109][110][111] Many patients with AD also have accompanying urticaria, dermatographism, and allergic rhinoconjunctivitis, and therefore they may be benefited by the use of antihistamines for these concurrent medical problems. …”
Section: Discussionmentioning
confidence: 99%
“…In doppelblinden, placebokontrollierten Studien zeigten Erhebungen älteren Datums keine signifikante Wirkung nicht-sedierender Antihistaminika [4,5]. Neuere Studien wollen hingegen eine Wirksamkeit nachweisen [6,7]. Nach unserer klinischen Erfahrung zeigen die Patienten sehr starke interindividuelle Variationen im Ansprechen auf Antihistaminika.Während bei einigen Patienten selbst die stärkeren sedierenden Antihistaminika keinen juckreizlindernden Effekt hervorrufen, zeigt sich ein sedativer Effekt und eine Juckreizreduktion bei anderen Patienten schon auf nichtsedierende Antihistaminika.…”
Section: Introductionunclassified